FIND THE ANSWERS

F(x) = 3x; g(x) = 4x^2 + 1 what expression is equal to (f•g)(x)?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • F(x) = 3x; g(x) = 4x^2 + 1 what expression is equal to (f•g)(x)?


Answers

... Give f(x)=3x^2+4x-1 and g(x) ... =3x^2+4x-1 and g(x)=x+3 simplify the expression when possible f(-3) (g degree sign f)(-1/2)
Read more
Positive: 94 %
A http://www.door2math.com production.Given f(x)=3x+2 and g(x)=2x^2-1 find the following and state if te composite function exists.? a) a) ( f o ...
Read more
Positive: 91 %

More resources

f(g(x)) = f(x − 2) = (x − 2) ... y = 3x − 4. Then we can invert it ... f(g(x)) = −½(−2x + 2) + 1 = x − 1 + 1 = x. and. g(f(x)) = −2 ...
Read more
Positive: 94 %
Performing these operations on functions is no more complicated than the notation itself. For ... Given f(x) = 3x + 2 and g(x) ... (f + g)(x) = f(x) ...
Read more
Positive: 89 %
... (x) = 5x - 3. Find (f - g)(x), (f - g)(x), (f middot g)(x), and (f/g) (x ... Find (f g)(x) and (g f)(x) f(x) = 3x + 2, g(x ... Rewrite the model with x ...
Read more
Positive: 75 %
Let f(x) = (x^2+3x-4) and g(x) = (x+4) Find f*g and state the domain. ... (x^2+3x-4)(x+4) The first expression can be ... But for all x not equal to -4 f/g ...
Read more
Positive: 52 %

Show more results

Anonymous15238
Login to your account
Create new account